ANALISA DEVINISI KAPAL IKAN PURSE SEINE 109 GT KM. SURYA REDJEKI - Wibawa BS, Ari (Department of Naval Architecture - Diponegoro University, 2010)
Traditional ship has so many kinds, It can be seen on every beach in Indonesia which has different ship design.this development ship design changes based on the ancestors' experiences and the miths believed by the society. Their belief in technology development is low. Therevore, the existance of education institution and research haven't yet had any role in design development of their ships. In this study, the goal is to analyze the resistance of hullform, stability analysis of hullform ship, and seakeeping performance (having, pitching, rolling) of the hullform ship. The ship identification was done for one of MV.Surya Redjeki ships using puersiene. The Data gathered then is used to revew hullform ship by using delfship software. Then,the picture is imported to IGS shape to get the result of resistance, stability, and moving. The result of running any software above is used as basic of counting to know the characteristic of MV. Surya Redeki Ship. Based on the counting and analisation, then, the MV.Surya Redjeki ship has total resistance with maximum running, stability is based on criteria standard IMO, for the highest movement is happen when using the biggest rolling.